The effect of uniform scattered genetic algorithms to window function performance - Kaya, Turgay; Ince, Melih Cevdet (My University, 2010)
In this study, the effects of Genetic Algorithms (GA) having uniform scattered initial population was analysed to window function performance used at design of finite impulse response filter prefered for many areas. At work, the comparison with amplitude response of Kaiser window having many features was done. With this work, GAs having different initial population were used to obtain more useful window function at calculation of suitable spectral parameter values. The obtained results show that to get result, uniform scattered GA is more successful than having random produced population. Addition, obtained results were shown with figures and were compared with Kaiser window results and finally, it was observed that the improved method for some applications has more useful structure. ©2010 IEEE.
Düzgün da?ilimli genetik algoritmalarin pencere fonksiyonu performansina etkisi
18th IEEE Signal Processing and Communications Applications Conference, SIU 2010 -- 22 April 2010 through 24 April 2010 -- Diyarbakir -- 83388
Keywords: FIR filters; Impulse response; Signal processing; Amplitude response; Finite impulse response filter; Improved methods; Initial population; Kaiser window; Spectral parameters; Window functions; Genetic algorithms